KAJIAN SISTEM RELIGI DAN NILAI PENDIDIKAN MORAL DALAM NOVEL MELANGKAH KARYA J. S. KHAIREN - Nama Penulis, Nama Penulis (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2023)
This study aims to describe and explain (1) the intrinsic elements of J. S. Khairen’s Melangkah novel, (2) Religious System in J. S. Khairen’s Melangkah novel, (3) and the moral education values ​​contained in the novel Melangkah by J. S. Khairen. The method used in this research is a qualitative method by using literary anthropology studies. The data collection technique was carried out by reading, and notes by identifying, The data source in this research is the novel Melangkah by J. S. Khairen issued by Grasindo in 2020 and 352 pages thick. The results of this study show (1) intrinsic elements in the form of theme, namely loyal friendship, the character consists Runa and Aura and 24 additional figures, the plot used the forward flow, the setting dominant in Kota Kembang and Sumba, the point of view used angle third person view using the pronouns; (2) the religious system of Sumba community, namely Marapu people believes the belief in existence of animism, dynamism and totemism. The religious ceremony system carried out includes Hamayang to worship the spirits of ancestors, Pasola festival and Wolla Mpoddu and sing the Holy Holy Song to welcome the arrival of guests or men and youth after war; and (3) ) the value of moral education in the novel in the form of human relations with his Lord is shown the obedience of a servant to his Lord as a manifestation of beliefs and obedience. Human relations with yourself indicate the manifestation of the characteristics or identity as a human being. Human relations with other humans in the social scope and natural environment indicate a reciprocal relationship between humans and nature to meet the needs of social life. Keywords: novel, religious systems, moral value, intrinsic elements